The Effect of Elections on Capital Expenditure and Social Assistance Expenditure - Yeni Eva Damayanti; Ahmad Karim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
The purpose of this study is to determine differences in the allocation of capital expenditure and social assistance expenditure before and during the local elections. This study uses Wilcoxon test as non parametric test. The results show that the proportion of capital expenditure and social assistance expenditure at the time of the election is not greater than the proportion of capital expenditure and social assistance expenditure at the prior to the election. But, there is not difference the proportion of capital expenditure at the time of the election is as well as at the prior to the election.